Management Motifs An Interactionist Approach for the Study of Organizational Interchange - Grills, Scott; Prus, Robert; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book examines management and management-related activities as a feature of everyday life. Any person or group that attempts to influence or shape the behaviors or experiences of others may be understood as engaging in management activities. The study of management involves the study of achieving understanding, providing direction and coordinating activities with others across an endless array of humanly engaged terrains. Management Motifs provides a research agenda for an interactionist approach to the study of management activities. Moving well beyond more organizationally-based understandings of managers and management, it examines the pragmatic accomplishment of management activities and the generic social processes that accompany them. This work addresses diverse issues related to management such as: holding and doing office, pursuing cooperation, developing policy, envisioning and advocating for missions, establishing teams and generating team identities, sustainingteam endeavors and managing self. By attending to management-related concerns as a generic feature of human group life, the authors develop and articulate a research framework for the study of managing and management.
Chapter 1. Management in the Making: The Pervasive and Enduring Challenge -- Chapter 2. Overviewing the Literature -- Chapter 3. Human Knowing and Acting -- Chapter 4. Engaging Office -- Chapter 5. Maintaining Continuities -- Chapter 6. Implementing Collective Ventures: Missions and Teams -- Chapter 7. Sustaining Team Endeavors -- Chapter 8. Managing Self: Processes and Problematics of Self-Regulation -- Chapter 9. The Ethnographic Venture.
Keywords: Industrial sociology; Strategic planning; Leadership; Personality; Difference (Psychology).; Sociology of Work; Business Strategy and Leadership; Personality and Differential Psychology